Peran dan Kedudukan Masyarakat Sebagai Landasan Pendidikan Islam Dalam Perspektif Sosiologi - Irsa Fitrianur Hijrah; Syarifah Nur Aini (Innovative: Journal Of Social Science Research, 2023)
This paper aims to map the concept, role and position of the community as part of the foundation of Islamic education through a sociological perspective based on the concept that society is the third educational institution after education in the family and school environment. Society plays a very important role in the development of children's education. Therefore the community should participate in children's educational activities either directly or indirectly. Because the environment in the family, and school and society is very attached. This study used an analytical descriptive method by examining references sourced from the library. In this study it was concluded that the role and position of the community as part of the foundation of Islamic education through a sociological perspective is related to (1) improving the quality of education by contributing, contributing ideas, input, criticism, and community participation in the activity process, including also about (2) creating a conducive social environment for education. (3) Revitalization and reorientation in Islamic education, especially for families and family members. (4) Strengthening Learning Society. (5) Participate actively in Madrasah/School Committees (6) Encourage and support all Religious Education programs in madrasas/schools Establish quality-based religious education institutions.